2015
DOI: 10.1002/tox.22114
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure to aluminum and acrylamide disturbs expression of metallothionein, proinflammatory cytokines and induces genotoxicity: Biochemical and histopathological changes in the kidney of adult rats

Abstract: The individual toxic effects of aluminum and acrylamide are known but there is no data on their combined effects. The present study investigates the toxic effects after combined exposure to these toxicants on: (i) oxidative stress during combined chronic exposure to aluminum and acrylamide on kidney function (ii) correlation of oxidative stress with metallothionein (MT) and inflammatory cytokines expression, DNA damage, and histopathological changes. Rats were exposed to aluminum (50 mg/kg body weight) in drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…After this glomerular filtration, between 40% and 60% is reabsorbed at the tubular level, constituting a marker of renal function [ [17] , [18] , [19] ]. In the present study, blood urea was elevated in acrylamide-treated rats (50 mg/kg), suggesting kidney damage [ [20] , [21] , [22] , [23] ]. Another metabolite that was analyzed in the present study was creatinine.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…After this glomerular filtration, between 40% and 60% is reabsorbed at the tubular level, constituting a marker of renal function [ [17] , [18] , [19] ]. In the present study, blood urea was elevated in acrylamide-treated rats (50 mg/kg), suggesting kidney damage [ [20] , [21] , [22] , [23] ]. Another metabolite that was analyzed in the present study was creatinine.…”
Section: Discussionmentioning
confidence: 64%
“…Its elimination is exclusively renal, so there is a correlation between creatinine levels and renal function. Most creatinine that is eliminated by the kidneys is freely filtered in renal glomeruli, and a small fraction is filtered by the tubular component, which is a good indicator of renal-glomerular function [ 17 , [21] , [22] , [23] ]. Similar to urea, creatinine and BUN significantly increased in rats that received acrylamide (25 and 50 mg/kg), indicating imminent kidney damage.…”
Section: Discussionmentioning
confidence: 99%
“…Acrylamide and aluminum (Al) are recognized worldwide as serious environmental contaminants. Coexposure to these compounds caused toxicity in soft tissues like liver (Ghorbel et al 2015a), kidney (Ghorbel et al 2015b), and heart (Ghorbel et al 2015c) of adult rats. The most usual Al exposure for the general population is through the diet, mainly from dietary additives (Fekete et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The cells lining renal tubules showed cytoplasmic vacuolations and loss of brush borders. 35,36 Our results from ACR-treated group revealed that the renal corpuscle appeared with significant increase in the amount of collagen fibers deposition among its glomerular capillaries. This is can explain by, ACR induced oxidative stress, resulting in generation of reactive oxygen species ROS which plays a critical role in the initiation and progression of fibrotic diseases.…”
Section: Discussionmentioning
confidence: 65%